2022
DOI: 10.3390/economies10020030
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tax Compliance Intention among Jordanian SMEs: A Focus on the Theory of Planned Behavior

Abstract: The present study aimed to adopt the extended theory of planned behavior (TPB) to determine the intentions of owner-managers in SMEs towards engaging in sales tax compliance. The study distributed a total of 660 questionnaire copies through systematic random sampling to the mangers/owners of Jordanian manufacturing SMEs, from which 385 questionnaire copies were retrieved and considered useable and appropriate for further analysis. The study made use of Partial-Least Squares-Structural Equation Modeling (PLS-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 105 publications
1
37
0
Order By: Relevance
“…Prior to the actual study, a pilot study was conducted on the instrument by distributing it to 40 SMEs that responded voluntarily to the request and were later excluded from the actual survey. The findings of the pilot study established the validity, reliability, and translation equivalence of the scale (Alshira'h & Abdul-Jabbar, 2020;Bani-Khalid et al, 2022).…”
Section: Measurements Sampling and Data Collectionmentioning
confidence: 73%
“…Prior to the actual study, a pilot study was conducted on the instrument by distributing it to 40 SMEs that responded voluntarily to the request and were later excluded from the actual survey. The findings of the pilot study established the validity, reliability, and translation equivalence of the scale (Alshira'h & Abdul-Jabbar, 2020;Bani-Khalid et al, 2022).…”
Section: Measurements Sampling and Data Collectionmentioning
confidence: 73%
“…Accuracy was established by conducting statistical power analyses for the estimate of sample size based on Cohen [97], and this was calculated using a priori power analysis with G* Power software. A sample size of 96 respondents was needed to obtain an alpha of 0.05, a moderate effect size of 0.15 and a power of 0.80, and because the sample size was comprised of 101 responses, it was deemed appropriate for SEM-PLS analysis [8,98,99]. Survey questionnaire procedures for the respondents are detailed in Figure 2.…”
Section: Data Collectionmentioning
confidence: 99%
“…Thus, IT/IS usage can pave the way for opportunities and benefits for both large and medium-sized (SMEs) businesses [6,7]. SMEs have jumped on the bandwagon of businesses searching for new methods to improve their productivity and maintain their competitiveness [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused their analyses on tax compliance among SMEs [21][22][23][24][25][26][27] and shown that tax compliance costs depend on the age of the firm, location and business activity. Furthermore, tax compliance behaviour is positively related to tax fairness, peer influence and political instability [28,29].…”
Section: Literature Reviewmentioning
confidence: 99%